(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
India is a fascinating case study in happiness. Because of its remarkable history, fast economic development, huge population, and ethnic, religious, and linguistic variety, it is a one-of-a-kind civilization. In this chapter, we look at happiness as both a "outside-in" and "inside-out" phenomena, and we put it in the context of India. We examine poll data on Indians’ life satisfaction from the outside in, finding that they are moderately happy but may grow more so if policies are established to provide employment and infrastructure to more people. We look at the various ways that subtle culture influences individual happiness from the inside out. Finally, we provide suggestions for happiness-related treatments. The findings in this area are significant not just for their contribution to our knowledge of human behavior, but also for their policy implications. While Bhutan may very well have taken a risk by coining the phrase Using the phrase ’Gross National Happiness,’ a play on the more often used term ’Gross National Product,’ a growing number of economists are realizing that happiness surveys might help governments make better decisions.